THE IMPROVEMENT OF SEMEN QUALITY AND TESTOSTERONE LEVEL OF BALI CATTLE AFTER PROSTAGLANDIN F2α ADMINISTRATION - Eka Meutia Sari; Satria Tanjung; Dewi Ratna Sari; Muslim Akmal; Tongku Nizwan Siregar; Cut Nila Thasmi (Universitas Syiah Kuala, 2019)
This study aimed to determine the effect of prostaglandin F2α (PGF2α) administration on improving semen quality and testosterone levels on Bali cattle. This study used 3 Bali cattle aged 2, 3.5, and 5 years old. The sample used in this study was Bali cattle semen. In this study, the Latin Square Design was used with three different treatments were administered over three time periods. The treatments performed were P1 (5 mL physiological NaCl), P2 (25 mg prostaglandin), and P3 (37.5 mg prostaglandin) while treatment period was three weeks of treatment administration, which were 1st. 2nd, and 3rd week. Blood collected through coccygea vein 30 minutes after treatment to measure testosterone levels using enzyme-linked immunosorbent assay (ELISA) technique. Statistical analysis showed that PGF2α administration at a dose of 25 mg and PGF2α at a dose of 37.5 mg had no effect (P0.05) on volume, color, pH, consistency, concentration, and motility of Bali cattle spermatozoa. The volume of semen obtained from P1; P2; and P3 were 6.5±0.9; 6.3±0.6; and 6.2±1.2 mL, respectively. The color of the semen in P1, P2, and P3 were beige and milky white. The pH in groups P1; P2; and P3 were 6.7±0.6; 7.1±0.2; and 6.5±0.2, respectively. Spermatozoa concentration in P1; P2; and P3 were 1,328±96.43 x 106 cells/mL; 1,354±102.19 x 106 cells/mL; and 1,353.3±88.55 x 106 cells/mL, respectively. Spermatozoa motility in P1; P2; and P3 were 73.3±2.8%; 71.6±2.8%; and 73.3±2.8%, respectively. Testosterone levels in P1 and P3 were 5.05±0.22 and 6.74±1.38 ng/mL, respectively (P0.05). Based on the results of this study, it was concluded that the administration of PGF2α does not affect semen quality but can increase the level of testosterone on Bali cattle.